BI’AH ‘ARABIYAH - Putri, Neli (AT-TA'LIM, 2013)
Bi’ah arabiyah is environment in which someone interacts with the other people by using Arabic.  It serves an important factor for anyone to acquire the language either as the first or second language.  The acquisition of Arabic as a second language especially in oral form takes place in the Arabian environment.  It can be realized formally or informally on certain level of education.  The absence of this bi’ah  will unlikely promote language skills. Copyright © 2013 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v20i2.37